Categories and indices of analysis of teaching practice conceived as the mobilization of teaching knowledge in moments of experience (Revista Contexto & Educação, 2023)
In this work, the concept of “teaching practice” is discussed based upon an analytical conception wherein categories and indices are established a priori and based on a given theoretical foundation. It is argued that teaching practice can be analyzed through comprehensive categories conceptualized from a conception that considers moments of mobilization of teaching knowledge in terms of idealization, decision and materiality of this practice. More specific concepts that come together in these moments and their materiality in the corpus of analysis lead to a look at the sources and origins of teaching knowledge, learning concepts, educational objectives, teaching content, didactic, school curriculum, teaching action and pedagogical trends. It is contended that the set of categories and analysis indices discussed in this work can be a relevant conceptual instrument for investigation of the teaching practice.
Keywords: teaching knowledge, learning theories, educational objectives, didactic.